UJI FLAVONOID KUNYIT PUTIH (Curcuma zedoria) DAN KUNYIT KUNING (Curcuma longa) SEBAGAI SENYAWA ANTIBAKTERI Stahylococcus aureus - Farach Khanifah (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Introduction: Nosocomial infections are one of the causes of high morbidity and mortality rates in the world, both in developed and developing countries (Kusumayanti, 2017). The prevalence of nosocomial infections in Southeast Asia is 10.0%, the European region is 7.7%, the Western Pacific is 9.0% and the Middle East is 11.8% (WHO, 2013). Objectives: this study was to determine the results of the flavonoid test of Curcuma longa as an antibacterial compound of Staphylococcus aureus and to determine the results of the inhibitory test of white turmeric and yellow turmeric in inhibiting the growth of Staphylococcus aureus bacteria. Methods: This type of research is experimental with a pre-experimental research design (one shot case study). The sampling technique used in this research is total sampling. Results: the phytochemical screening test of white and yellow turmeric showed that both turmeric contained flavonoids which were indicated by the formation of a green color in the filtrate. The diameter of the inhibition zone of white turmeric (Curcuma zedoria) was 0.05 and yellow turmeric (Curcuma longa) was 0.7 against Staphylococcus aureus bacteria. Conclusion:Yellow turmeric (Curcuma longa) and white turmeric (Curcuma zedoria) extracts contain flavonoids and have the ability to inhibit the growth of Staphylococcus aureus bacteria more than white turmeric (Curcuma zedoria) juice. Keywords: Turmeric, Staphylococcus aureus, and Flavonoid Test.